An Investigation of Secondary School Students’ Scientific Conceptions of Frictional Force - สามารถ พิชิต; แนมจันทร์ กิตติศักดิ์ชัย; รัตนานุพงศ์ พันเทพ; ชูสกุล พชร; กลั่นบุศย์ แสงกฤช (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aims to design a test to measure scientific concepts regarding frictional force and to explore the misconceptions of a sample group of 73 Secondary school students for the academic year 2025 through a 4-item scientific concept survey covering two learning objectives. The survey passed quality checks and included a test that could be used to assess scientific concepts. The survey results showed that only 8% of students got the right scientific concept, and 93% of them thought that a larger contact area would lead to greater static frictional force. Additionally, the analysis of the misconceptions identified six key issues: (1) the size of frictional force is directly proportional to the applied force (40%), (2) objects with a larger contact area result in higher maximum static frictional force (83%), (3) objects with a larger contact area have a greater angle of inclination before they start moving (78%), (4) objects with a larger contact area have a higher coefficient of static frictional force (53%), (5) increasing the weight of an object results in a larger angle of inclination required for the object to start moving (48%), and (6) increasing the weight of an object results in a higher coefficient of static frictional force (34%).